Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai pada Badan Perencanaan Pembangunan Daerah Kota Bima - Mumtahnah; Mukhlis; Jaenab (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to determine the effect of work motivation and work discipline on employee performance at the Regional Development Planning Agency (BAPPEDA) of Bima City. The study uses a descriptive quantitative approach. The study population was 47 employees, with a sample of 41 Civil Servants (PNS) selected using a purposive sampling technique. Data were collected through observation, questionnaires, interviews, and literature studies, then analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, determination coefficients, t-tests, and F-tests. The results of the study indicate that work motivation and work discipline have a positive and significant effect on employee performance, both partially and simultaneously. This finding indicates that increasing work motivation and work discipline is an important factor in supporting employee performance improvement and achieving organizational goals effectively and efficiently. The implication of this study is the need for BAPPEDA of Bima City to strengthen human resource management policies through strategies to increase motivation and enforce work discipline on an ongoing basis in order to improve service quality and organizational performance.